Preliminary clinical outcomes of a short-term low-intensity Early Start Denver Model implemented in the Taiwanese public health system. (July 2020) - Lin, Tzu-Ling; Chiang, Chung-Hsin; Ho, Suk Yin; Wu, Hsin-Chi; Wong, Ching-Ching
The Early Start Denver Model is an evidence-based, comprehensive naturalistic developmental behavioral intervention. Randomized controlled studies indicate that long-term, high-intensity Early Start Denver Model in home-based settings can positively impact the clinical outcomes of young children with autism spectrum disorder. However, it is difficult to deliver high-intensity early intervention in an under-resourced country such as Taiwan. This study evaluated the effects of implementing the Early Start Denver Model with adaptations (including low intensity, shorter duration, and delivery in general hospitals by multidisciplinary professionals) within the Taiwanese public health system. A pre- and post-intervention study was conducted. Sixteen children with autism spectrum disorder (mean age of 33.5 months) received 6 months of one-on-one Early Start Denver Model intervention (approximately 8 h per week). The children showed significant post-intervention improvements in language and overall cognitive functioning and reduced symptom severity in communication and play. This study suggests that delivering the Early Start Denver Model in community-based hospitals may be an effective intervention, with a wider reach, for young children with autism spectrum disorder in Taiwan. The next steps in Taiwan are to incorporate a control group and assess the long-term effects of the adapted Taiwanese Early Start Denver Model program. Lay Abstract: The Early Start Denver Model is a comprehensive naturalistic developmental behavioral intervention for young children with autism spectrum disorder. Rigorous studies indicate that long-term, high-intensity Early Start Denver Model in home-based settings can help young children with autism spectrum disorder have great progress in language, cognitive development, and adaptive skills and reduce overall symptom severity. In accordance with the current limitations in resourcing for early intervention in Taiwan, this study evaluated the effects of implementing the Early Start Denver Model in the Taiwanese public health system with some adaptations, including lower intensity, shorter duration, and delivery in general hospitals. A total of 16 children with autism spectrum disorder, aged between 25 and 46 months, received approximately 8 h per week one-on-one Early Start Denver Model intervention. After 6 months of intervention, the children showed great improvements in language and overall cognitive functioning and reduced symptom severity in communication and play. This study suggests that directly delivering the Early Start Denver Model in community-based hospitals may be an effective intervention, which can make more young children with autism spectrum disorder in Taiwan access the Early Start Denver Model service.